Epidemiological investigation on the cervical health of lesbians in Beijing, China - Chen, Xiangfan (J Int Med Res, 2020)
OBJECTIVE: To investigate human papillomavirus (HPV) infection status and influencing factors among lesbians. METHODS: In August to October 2018, 300 lesbians were recruited in Beijing using snowball sampling. Sociodemographic characteristics, behavioural indices and HPV status were measured. Colposcopy was performed on participants with HPV genotypes 16 and 18 and on participants with other high-risk HPV subtypes and positive ThinPrep (TCT) results. RESULTS: The overall HPV-positive rate was 25%. High number of sexual partners, smoking, drinking, not using condoms and using sex toys during intercourse were identified as HPV infection risk factors. Of the HPV subtypes detected, 84% were high-risk HPV subtypes. The colposcopy results showed that 20 participants (80%) with HPV 16 and HPV 18 had cervical intraepithelial neoplasia I (CIN I) or above lesions. The colposcopy results also showed that 16 participants (64%) infected with other high-risk types of HPV virus and who had positive TCT results had CIN I or above lesions. CONCLUSIONS: The cervical health of lesbians should not be neglected, and appropriate health education should be improved for this group.